Pratiques Festives Des Brouteurs En Côte d'Ivoire Entre Ritualisation De La Fête Et Categorisation Sociale Du Cybercriminel - Bamba Ladji; Raymond Nébi Bazare (European Scientific Journal, ESJ, 2016)
This article aims to explain the social categorization mechanism that governs the world of cybercriminals. It is therefore a practical review of the "grazer" including festive practices (sex, alcohol, psychotropic, etc.) that the ethnographic approach allowed to do. The analysis of both qualitative and quantitative data, put light on the complexity of the social processes of the Ivorian typologisation cybercriminal and festive practices related thereto. Thus the daily "bulldozer" and the ritualistic nature of existing social practices were observed over one year (February 2012 - January 2013), among 250 respondents of which 100 criminals on all 10 districts of Abidjan. This allowed to go to the evidence that festive practices are the ends pursued scams grazers. They determine their belonging to a category of cybercriminals while strengthening the perpetuation of scams on the web activities.